Phytochemicals and Antibacterial Evaluation of Root Bark Extract of Terminalia glaucescens - JS Bulama, SM Dangoggo, YA Bwala, JO Abah (Journal of Applied Pharmaceutical Science, 2014)
The roots bark of Terminalia glaucescens was investigated for activity against four bacterial which are two gram- positive and two gram-negative. Preliminary phytochemical screening of the root bark of Terminalia glaucescens revealed the presence of steroids, terpenoids, saponins, flavonoids, tannins and cardiac glycoside. The results of antibacterial test of the methanol crude extract and its fractions exhibited a wide range of activity against Staphylococcus aureus, Escherichia coli and Klepselle pneumonia at 200 mg/ml but there was no activity against Bacillus cereus. Fractions inhibited the growth of E. coli, S. aureus and K. pneumonia. The fractions had minimum inhibitory concentration (MIC) of 12.5mg/ml and minimum bactericidal concentration (MBC) of 25 mg/ml. The findings indicated that the extract and its fractions from root bark of T. glaucescens, contained bioactive components that have antibacterial properties.
Keywords: Terminalia glaucescens, phytochemical screening, Escherichia coli and Klepselle pneumonia.